EYE-MOVEMENT METRICS OF COGNITIVE LOAD IN NAVAL COMMAND BRIDGE SETTING - Calbureanu-Popescu, Calin (My University, 2023)
This paper focused on pupillary activity and gaze-pattern similarity as reliable indicators of cognitive load inside a naval command bridge setting. Eleven seafarers in training were recruited, for testing a virtual reality simulation of a collision avoidance scenario. The subjects performed two scenarios of different difficulty, with the harder scenario being longer and consisting of an increase in the number of ships present in the scenario. The Varjo VR-2 headset’s eye-tracking system was used to measure the pupil size and the fixations of participants throughout both tasks. The analysis was performed by measuring the index of pupillary activity (IPA) and the scan-path of the subjects and comparing them from one difficulty to another. The results of this analysis have shown: (1) no significant difference in the index of pupillary activity between difficulties, and (2) no significant difference in gaze-pattern similarity within groups. These results should be considered with caution due to the small sample size; thus, further testing would better determine the reliability of these metrics as cognitive load indicators.
Keywords: Pupillary activity, Scanpath, Eye-tracking, Virtual Reality, Cognitive Load, Maritime Navigation